Evaluasi Kebijakan Pengawasan Keuangan Desa Pasca Implementasi Peraturan Menteri Dalam Negeri Nomor 73 Tahun 2020 Tentang Pengawasan Pengelolaan Keuangan Desa - Zaenudin Zaenudin; Hamdani Hamdani (Jurnal Eksplorasi Akuntansi, 2023)
Permendagri Number 73 of 2020 was established as an effort to strengthen village financial management. Law Number 6 of 2014 concerning Villages and their implementing regulations do not clearly and explicitly regulate the format and form of village financial supervision, resulting in several gaps in village financial supervision. The implementation of village financial supervision is not running as it should be due to the limited resources of the Regency/City APIP and the IT-based supervision system that is not yet optimal. At this time the Regency/City APIP in its PKPT still uses the sample method to carry out village financial supervision in one year and is post-audit in nature which is not in line with the spirit of APIP supervision which emphasizes when the activity is taking place. A critical review of Permendagri Number 73 of 2020 found two things that are research questions. First, this provision was not implemented properly by the Regency/Municipal APIP with consideration of limited resources and supervisory information technology. Second, the inspection program and procedures as stipulated in Permendagri Number 73 of 2020 are too detailed and detailed which requires audit implementers to go to the field (field audit), while APIP implementation can be carried out online because the Village Government has implemented an IT-based village finance application. The results of this research will answer some of the weaknesses of Permendagri Number 73 of 2020 as a Policy Brief to the Minister of Home Affairs to improve regulations.